(Z)-3-Ferrocenyl-2-(3-pyridyl)acrylonitrile - Chen, Fang (International Union of Crystallography, 2008)
The molecular structure of the title compound, [Fe(C(5)H(5))(C(13)H(9)N(2))], (I), is analogous to that of the compound (Z)-3-ferrocenyl-2-phenylacrylonitrile [Cao & Ye (2008). Acta Cryst. E64, m822], (II), with the pyridine ring in (I) replacing the benzene ring in (II). While the corresponding bond distances and angles in the two compounds show no significant differences, the two dihedral angles between the planes through the acrylonitrile group and the two rings attached to it (substituted Cp and pyridine) of 16.8 (4) and 20.1 (4)° in (I) are different from the corresponding dihedral angles [19.6 (3) and 6.5 (4)°] in (II). The unsubstituted ring is disordered over two positions, with site-occupancy factors of 0.70 (1) and 0.30 (1). The major and minor components of the disordered ring are almost coplanar and are also parallel to the substituted cyclopentadiene ring plane, with a dihedral angle of 0.3 (6)°.